Training supervisors to provide performance feedback using video modeling with voiceover instructions: A replication. Issue 2 (23rd February 2022) - Carroll, Regina A.; Preas, Elizabeth J.; Paden, Amber R.
Abstract : Performance feedback is an effective strategy to improve and maintain therapist performance with implementing interventions. Shuler and Carroll (2019) successfully used video modeling with voiceover instructions (VMVO) to train supervisors to provide accurate performance feedback to a confederate therapist implementing guided compliance. In Study 1, we replicated Shuler and Carroll by using VMVO to train 5 supervisors to provide performance feedback to a confederate therapist on their guided‐compliance integrity. Feedback accuracy increased following VMVO and maintained for 1 month. In Study 2, we extended Shuler and Carroll by demonstrating improvements in therapist guided‐compliance integrity after they received performance feedback from supervisors from Study 1. The results of the current study support the use of VMVO to teach supervisory skills to behavior analysts.